1996
DOI: 10.1007/bf01997720
|View full text |Cite
|
Sign up to set email alerts
|

Human heart rate variability and sleep stages

Abstract: With the aim of better understanding the dynamic changes in sympatho-vagal tone occurring during the night, human heart rate variability (HRV) during the various sleep stages was evaluated by means of autoregressive spectral analysis. Each recording consisted of an electroencephalogram, an electrooculogram, and electromyogram, and electrocardiogram, and a spirometry trace. All of the data were sampled and stored in digital form. Sleep was analysed visually, but HRV was analysed off-line by means of original so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 9 publications
5
42
0
Order By: Relevance
“…Contradictory results were noted in one of the studies that demonstrated significant difference in sample entropy between patients with mild and severe OSA, but failed to show significant differences between patients with severe OSA and subjects without OSA [30]. One explanation for the paradoxical finding may be the use of ECG signals during REM and NREM sleep for comparison without taking into account the different stages of sleep [30] that has been reported to affect autonomic nervous activities [16,31,32]. For a more accurate assessment, the present study decomposed sleep into different stages (i.e., N1-N3) and chose N2 for analysis because of sporadic distribution of stage N1 and usually short duration of stage N3.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results were noted in one of the studies that demonstrated significant difference in sample entropy between patients with mild and severe OSA, but failed to show significant differences between patients with severe OSA and subjects without OSA [30]. One explanation for the paradoxical finding may be the use of ECG signals during REM and NREM sleep for comparison without taking into account the different stages of sleep [30] that has been reported to affect autonomic nervous activities [16,31,32]. For a more accurate assessment, the present study decomposed sleep into different stages (i.e., N1-N3) and chose N2 for analysis because of sporadic distribution of stage N1 and usually short duration of stage N3.…”
Section: Discussionmentioning
confidence: 99%
“…High AHI individuals should also show more sympathetic activation [1,7] and either similar or increased parasympathetic activation compared to individuals with low AHI (hypothesis two). Finally, considering reports of differences in autonomic cardiac control between NREM and REM sleep [2,6], cardiac activity is expected to be significantly slower during NREM sleep than during REM sleep, mainly due to reciprocal parasympathetic activation and sympathetic inhibition during NREM. During REM sleep, the heart is expected to show sympathetic activation and parasympathetic inhibition compared to NREM (hypothesis three) [24].…”
Section: Introductionmentioning
confidence: 98%
“…During rapid-eye movement (REM) sleep, heart rate does not differ significantly from that of the wake state, but during non-REM (NREM) sleep, heart rate decreases progressively across the sleep period. This pattern has been associated with progressive sympathetic inhibition during all sleep stages, parasympathetic activation during NREM sleep, and parasympathetic inhibition during REM sleep [6][7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…The standard deviation of normal R-wave to R-wave intervals reflecting the overall heart rate variability is higher during REM sleep (Zemaityte et al, 1984;Cajochen et al, 1994;Pivik et al, 1996;Viola et al, 2002). The power of high frequency component in HRV increases whereas that of low frequency component decreases with the depth of sleep (Zemaityte et al, 1984;Baharav et al, 1995;Toscani et al, 1996;Scholz et al, 1997). However, some reports argued that the high frequency component in HRV has little relationship with sleep (Ako et al, 2003).…”
Section: Introductionmentioning
confidence: 93%